Improving pain management in neonates exposed to intravenous insertions: A quality improvement initiative. Issue 6 (December 2016) - Lagunas, Angelica M.; Hall, Heather R.
Abstract: Background: From the time a neonate is admitted into the neonatal intensive care unit (NICU), they are exposed to several painful procedures especially, intravenous (IV) catheter insertions. An increase use of sucrose is essential to improve pain management in neonates exposed to IV insertions. The proper administration and storage location of sucrose plays an integral role in neonatal pain management. Purpose: The purpose of implementing the quality improvement (QI) project is to improve the quality of care within the neonatal population by improving neonatal nurses' beliefs, knowledge, and practices regarding neonatal pain. Methods: A quality improvement process to re-locate sucrose from the Pyxis (medication dispenser) to central supply unit to increase sucrose usage was completed along with distributing a 40-item pre and post questionnaire regarding neonatal pain to a convenience sample of nurses in a level II/III NICU in the Southeast Florida region. Pre and post intervention observation audits were also utilized to differentiate practice change throughout the QI initiative in the level II NICU. Results: Twenty nurses agreed to participate in the QI initiative and completed both pre and post intervention questionnaires. Results reflect an increase in nurses' knowledge and beliefs and improved pain management practices. As a group, there was a significant difference between the utilization of sucrose two minutes prior to insertion of intravenous catheter (p < 0.05). The utilization of sucrose two minutes prior to insertion increased from 15% in the pre observations to 90% in the post observations. Conclusion: There is significant evidence that increased knowledge in neonatal pain management, the proper administration of sucrose including increased sucrose utilization will result in better pain management among neonates exposed to intravenous insertions.